Инструменты и средства Веб-поддержки традиционных курсов обучения физике - Кузнецов С. И. Сергей Иванович; Маерков П. О. Павел Олегович; Рогозин К. И. Константин Иванович; Пшенова У. Ульяна (2014, 2014)
Заглавие с экрана